Intestinal Protective Efficacy of Gamma Co-60 Irradiated Chitosan and Vitamin E Combination on Lead acetate-induced Rats - Aditya Marianti; Edward Louis Krey; Wulan Christijanti; Lisdiana Lisdiana (Biosaintifika: Journal of Biology & Biology Education, 2022)
As an organ that absorbs food, the intestine can be damaged when interacting directly with lead (Pb). Gamma Co-60 irradiated chitosan, and vitamin E combination potentially can help reduce free radical damage to intestinal organs. This study examines the efficacy of gamma Co-60 irradiated chitosan and vitamin E combination in protecting the intestinal tissue of rats exposed to Pb acetate. The 24 rats were grouped into 6 groups, each 4 rats; were induced with Pb acetate, except the control group. The negative control group was only induced Pb acetate. The positive control group had additional treatment of irradiated chitosan. The treatment group (1-3) was treated using the combination of gamma Co-60 irradiated chitosan at a dose of 64 mg/kg BW and vitamin E 1000 IU at a dose of 1.44; 2.16, 3.00 mg/kg BW, respectively, for forty days. The research parameters observed are edema, degeneration, necrosis, erosion of the intestinal villi, and lysis of the intestinal villi. Intestinal histology appearance data in all groups were analyzed descriptively. The result shows that a combination of Gamma Co-60 irradiated chitosan at a dose of 64 mg/kg BW and vitamin E at a dose of 1.44 mg/kg BW effectively reduced lead cytotoxicity in the intestinal tissue of Pb acetate-induced rats. The larger the dose of vitamin E has the potential to produce pro-oxidants, which will increase the toxic effect on intestinal tissue. Gamma Co-60 irradiated chitosan, and vitamin E combination at the right dose has the potential to be developed as a supplement to reduce the toxic effects of chronic lead exposure. Especially for people who, for some reason, cannot avoid chronic lead exposure.